Case Report: Interleukin-2 Receptor Common Gamma Chain Defect Presented as a Hyper-IgE Syndrome - Belaid, Brahim; Lamara Mahammed, Lydia; Mohand Oussaid, Aida; Migaud, Melanie; Khadri, Yasmine; Casanova, Jean Laurent; Puel, Anne; Ben Halla, Nafissa; Djidjik, Reda (Frontiers in Immunology, 2021)
X-linked severe combined immunodeficiency (X-SCID) is caused by mutations of IL2RG, the gene encoding the interleukin common gamma chain (IL-2Rγ or γc) of cytokine receptors for interleukin (IL)-2, IL-4, IL-7, IL-9, IL-15, and IL-21. Hypomorphic mutations of IL2RG may cause combined immunodeficiencies with atypical clinical and immunological presentations. Here, we report a clinical, immunological, and functional characterization of a missense mutation in exon 1 (c.115G>A; p. Asp39Asn) of IL2RG in a 7-year-old boy. The patient suffered from recurrent sinopulmonary infections and refractory eczema. His total lymphocyte counts have remained normal despite skewed T cell subsets, with a pronounced serum IgE elevation. Surface expression of IL-2Rγ was reduced on his lymphocytes. Signal transducer and activator of transcription (STAT) phosphorylation in response to IL-2, IL-4, and IL-7 showed a partially preserved receptor function. T-cell proliferation in response to mitogens and anti-CD3/anti-CD28 monoclonal antibodies was significantly reduced. Further analysis revealed a decreased percentage of CD4+ T cells capable of secreting IFN-γ, but not IL-4 or IL-17. Studies on the functional consequences of IL-2Rγ variants are important to get more insight into the pathogenesis of atypical phenotypes which may lay the ground for novel therapeutic strategies.